EVALUASI KEMAMPUAN FISIK WASIT SEPAK BOLA C3 ASKAP PSSI ACEH BESAR - Saputra, Reza; Kurniawan, Erizal; Syahrianursaifi, Syahrianursaifi; Musran, Musran; Husaini, Husaini (Jurnal Dedikasi Pendidikan, 2024)
Football referees are required to have good physical abilities in order to be able to lead the match. Good physical condition allows the referee to always be close to the ball that is being played and able to clearly see all events on the field. Aceh Besar football referees still often make mistakes in decision making, the referee is far from the ball making it difficult to see the offense. The purpose of this study was to determine the results of the evaluation of the physical abilities of the C3 Askab PSSI Aceh Besar Football Referee. This study uses a quantitative approach with the type of evaluation, The population and sample in this study were C3 Askab referees totaling 20 people with purposive sampling technique. The research data collection instruments are: 1) Running speed test 6 x 40 meters, 2) Interval test 40 x 75 meters. Data is analyzed using percentages. The research results obtained are, 1) The average running speed of the C3 Askap football referee is 5.516 seconds classified as a very good category (85%), and 2) The average cardiopulmonary endurance of the C3 Askap football referee 17.05 is classified as a very good category (65%). The conclusion of this study is that the physical abilities of the C3 Askab PSSI Aceh Besar Football Referee are very good